5.9.14 Problems 1301 to 1400

Table 5.655: First order ode linear in derivative

#

ODE

Mathematica

Maple

3671

\[ {}y^{\prime }+y \cot \left (x \right ) = y^{3} \sin \left (x \right )^{3} \]

3672

\[ {}y^{\prime } = \left (9 x -y\right )^{2} \]

3673

\[ {}y^{\prime } = \left (4 x +y+2\right )^{2} \]

3674

\[ {}y^{\prime } = \sin \left (3 x -3 y+1\right )^{2} \]

3675

\[ {}y^{\prime } = \frac {y \left (\ln \left (x y\right )-1\right )}{x} \]

3676

\[ {}y^{\prime } = 2 x \left (x +y\right )^{2}-1 \]

3677

\[ {}y^{\prime } = \frac {x +2 y-1}{2 x -y+3} \]

3678

\[ {}y^{\prime }+p \left (x \right ) y+q \left (x \right ) y^{2} = r \left (x \right ) \]

3679

\[ {}y^{\prime }+\frac {2 y}{x}-y^{2} = -\frac {2}{x^{2}} \]

3680

\[ {}y^{\prime }+\frac {7 y}{x}-3 y^{2} = \frac {3}{x^{2}} \]

3681

\[ {}\frac {y^{\prime }}{y}+p \left (x \right ) \ln \left (y\right ) = q \left (x \right ) \]

3682

\[ {}\frac {y^{\prime }}{y}-\frac {2 \ln \left (y\right )}{x} = \frac {1-2 \ln \left (x \right )}{x} \]

3683

\[ {}\sec \left (y\right )^{2} y^{\prime }+\frac {\tan \left (y\right )}{2 \sqrt {1+x}} = \frac {1}{2 \sqrt {1+x}} \]

3684

\[ {}y \,{\mathrm e}^{x y}+\left (2 y-x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0 \]

3685

\[ {}\cos \left (x y\right )-x y \sin \left (x y\right )-x^{2} \sin \left (x y\right ) y^{\prime } = 0 \]

3686

\[ {}y+3 x^{2}+x y^{\prime } = 0 \]

3687

\[ {}2 x \,{\mathrm e}^{y}+\left (3 y^{2}+x^{2} {\mathrm e}^{y}\right ) y^{\prime } = 0 \]

3688

\[ {}2 x y+\left (x^{2}+1\right ) y^{\prime } = 0 \]

3689

\[ {}y^{2}-2 x +2 x y y^{\prime } = 0 \]

3690

\[ {}4 \,{\mathrm e}^{2 x}+2 x y-y^{2}+\left (x -y\right )^{2} y^{\prime } = 0 \]

3691

\[ {}\frac {1}{x}-\frac {y}{x^{2}+y^{2}}+\frac {x y^{\prime }}{x^{2}+y^{2}} = 0 \]

3692

\[ {}y \cos \left (x y\right )-\sin \left (x \right )+x \cos \left (x y\right ) y^{\prime } = 0 \]

3693

\[ {}2 y^{2} {\mathrm e}^{2 x}+3 x^{2}+2 y \,{\mathrm e}^{2 x} y^{\prime } = 0 \]

3694

\[ {}y^{2}+\cos \left (x \right )+\left (2 x y+\sin \left (y\right )\right ) y^{\prime } = 0 \]

3695

\[ {}\sin \left (y\right )+y \cos \left (x \right )+\left (x \cos \left (y\right )+\sin \left (x \right )\right ) y^{\prime } = 0 \]

3928

\[ {}y^{\prime }-2 y = 6 \,{\mathrm e}^{5 t} \]

3929

\[ {}y^{\prime }+y = 8 \,{\mathrm e}^{3 t} \]

3930

\[ {}y^{\prime }+3 y = 2 \,{\mathrm e}^{-t} \]

3931

\[ {}y^{\prime }+2 y = 4 t \]

3932

\[ {}y^{\prime }-y = 6 \cos \left (t \right ) \]

3933

\[ {}y^{\prime }-y = 5 \sin \left (2 t \right ) \]

3934

\[ {}y^{\prime }+y = 5 \,{\mathrm e}^{t} \sin \left (t \right ) \]

3956

\[ {}y^{\prime }+2 y = 2 \operatorname {Heaviside}\left (t -1\right ) \]

3957

\[ {}y^{\prime }-2 y = \operatorname {Heaviside}\left (t -2\right ) {\mathrm e}^{t -2} \]

3958

\[ {}y^{\prime }-y = 4 \operatorname {Heaviside}\left (t -\frac {\pi }{4}\right ) \sin \left (t +\frac {\pi }{4}\right ) \]

3959

\[ {}y^{\prime }+2 y = \operatorname {Heaviside}\left (t -\pi \right ) \sin \left (2 t \right ) \]

3960

\[ {}y^{\prime }+3 y = \left \{\begin {array}{cc} 1 & 0\le t <1 \\ 0 & 1\le t \end {array}\right . \]

3961

\[ {}y^{\prime }-3 y = \left \{\begin {array}{cc} \sin \left (t \right ) & 0\le t <\frac {\pi }{2} \\ 1 & \frac {\pi }{2}\le t \end {array}\right . \]

3962

\[ {}y^{\prime }-3 y = -10 \,{\mathrm e}^{-t +a} \sin \left (-2 t +2 a \right ) \operatorname {Heaviside}\left (t -a \right ) \]

3971

\[ {}y^{\prime }-y = \left \{\begin {array}{cc} 2 & 0\le t <1 \\ -1 & 1\le t \end {array}\right . \]

3972

\[ {}y^{\prime }-y = \left \{\begin {array}{cc} 2 & 0\le t <1 \\ -1 & 1\le t \end {array}\right . \]

3973

\[ {}y^{\prime }+y = \delta \left (t -5\right ) \]

3974

\[ {}y^{\prime }-2 y = \delta \left (t -2\right ) \]

3975

\[ {}y^{\prime }+4 y = 3 \delta \left (t -1\right ) \]

3976

\[ {}y^{\prime }-5 y = 2 \,{\mathrm e}^{-t}+\delta \left (t -3\right ) \]

4077

\[ {}5 x y+4 y^{2}+1+\left (x^{2}+2 x y\right ) y^{\prime } = 0 \]

4078

\[ {}2 x \tan \left (y\right )+\left (x -x^{2} \tan \left (y\right )\right ) y^{\prime } = 0 \]

4079

\[ {}y^{2} \left (x^{2}+1\right )+y+\left (2 x y+1\right ) y^{\prime } = 0 \]

4080

\[ {}4 x y^{2}+6 y+\left (5 x^{2} y+8 x \right ) y^{\prime } = 0 \]

4081

\[ {}5 x +2 y+1+\left (2 x +y+1\right ) y^{\prime } = 0 \]

4082

\[ {}3 x -y+1-\left (6 x -2 y-3\right ) y^{\prime } = 0 \]

4083

\[ {}x -2 y-3+\left (2 x +y-1\right ) y^{\prime } = 0 \]

4084

\[ {}6 x +4 y+1+\left (4 x +2 y+2\right ) y^{\prime } = 0 \]

4085

\[ {}3 x -y-6+\left (x +y+2\right ) y^{\prime } = 0 \]

4086

\[ {}2 x +3 y+1+\left (4 x +6 y+1\right ) y^{\prime } = 0 \]

4090

\[ {}x^{2} y^{\prime } = x \left (y-1\right )+\left (y-1\right )^{2} \]

4091

\[ {}y^{\prime } = {\mathrm e}^{-x} \]

4092

\[ {}y^{\prime } = 1-x^{5}+\sqrt {x} \]

4093

\[ {}3 y-2 x +\left (3 x -2\right ) y^{\prime } = 0 \]

4094

\[ {}x^{2}+x -1+\left (2 x y+y\right ) y^{\prime } = 0 \]

4095

\[ {}{\mathrm e}^{2 y}+\left (1+x \right ) y^{\prime } = 0 \]

4096

\[ {}\left (1+x \right ) y^{\prime }-x^{2} y^{2} = 0 \]

4097

\[ {}y^{\prime } = \frac {y-2 x}{x} \]

4098

\[ {}x^{3}+y^{3}-y^{2} y^{\prime } x = 0 \]

4099

\[ {}y^{\prime }+y = 0 \]

4100

\[ {}y^{\prime }+y = x^{2}+2 \]

4101

\[ {}y^{\prime }-\tan \left (x \right ) y = x \]

4102

\[ {}y^{\prime } = {\mathrm e}^{x -2 y} \]

4103

\[ {}y^{\prime } = \frac {x^{2}+y^{2}}{2 x^{2}} \]

4104

\[ {}x y^{\prime } = x +y \]

4105

\[ {}{\mathrm e}^{-y}+\left (x^{2}+1\right ) y^{\prime } = 0 \]

4106

\[ {}y^{\prime } = {\mathrm e}^{x} \sin \left (x \right ) \]

4107

\[ {}y^{\prime }-3 y = {\mathrm e}^{3 x}+{\mathrm e}^{-3 x} \]

4108

\[ {}y^{\prime } = x +\frac {1}{x} \]

4109

\[ {}x y^{\prime }+2 y = \left (3 x +2\right ) {\mathrm e}^{3 x} \]

4110

\[ {}2 \sin \left (3 x \right ) \sin \left (2 y\right ) y^{\prime }-3 \cos \left (3 x \right ) \cos \left (2 y\right ) = 0 \]

4111

\[ {}x y y^{\prime } = \left (1+x \right ) \left (1+y\right ) \]

4112

\[ {}y^{\prime } = \frac {2 x -y}{y+2 x} \]

4113

\[ {}y^{\prime } = \frac {3 x -y+1}{3 y-x +5} \]

4114

\[ {}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0 \]

4115

\[ {}x +\left (2-x +2 y\right ) y^{\prime } = x y \left (y^{\prime }-1\right ) \]

4116

\[ {}\cos \left (x \right ) y^{\prime }+y \sin \left (x \right ) = 1 \]

4117

\[ {}\left (y^{2}+x \right ) y^{\prime }+y-x^{2} = 0 \]

4190

\[ {}y y^{\prime } = x \]

4191

\[ {}y^{\prime }-y = x^{3} \]

4192

\[ {}y^{\prime }+y \cot \left (x \right ) = x \]

4193

\[ {}y^{\prime }+y \cot \left (x \right ) = \tan \left (x \right ) \]

4194

\[ {}y^{\prime }+\tan \left (x \right ) y = \cot \left (x \right ) \]

4195

\[ {}y^{\prime }+y \ln \left (x \right ) = x^{-x} \]

4196

\[ {}x y^{\prime }+y = x \]

4197

\[ {}x y^{\prime }-y = x^{3} \]

4198

\[ {}x y^{\prime }+n y = x^{n} \]

4199

\[ {}x y^{\prime }-n y = x^{n} \]

4200

\[ {}\left (x^{3}+x \right ) y^{\prime }+y = x \]

4201

\[ {}\cot \left (x \right ) y^{\prime }+y = x \]

4202

\[ {}\cot \left (x \right ) y^{\prime }+y = \tan \left (x \right ) \]

4203

\[ {}\tan \left (x \right ) y^{\prime }+y = \cot \left (x \right ) \]

4204

\[ {}\tan \left (x \right ) y^{\prime } = y-\cos \left (x \right ) \]

4205

\[ {}y^{\prime }+y \cos \left (x \right ) = \sin \left (2 x \right ) \]

4206

\[ {}\cos \left (x \right ) y^{\prime }+y = \sin \left (2 x \right ) \]